Hak atas Pangan dalam Konstitusionalisme Global: Studi Komparatif Pengaturan dan Implementasi di Indonesia dan Brasil - Farah Alif Nabila; Jadmiko Anom Husodo; Isharyanto Isharyanto (Res Publica: Jurnal Hukum Kebijakan Publik, 2026)
This article examines the constitutional regulation of the right to food in Indonesia and Brazil by situating food as an economic, social, and cultural right inseparable from human dignity, survival, and welfare. Central issue is the contrast between Indonesia’s implicit constitutional model, in which the right to food is derived from the rights to life, decent livelihood, and physical and spiritual welfare under the 1945 Constitution, and Brazil’s explicit model, which incorporates food as a social right under Article 6 of the 1988 Federal Constitution after Constitutional Amendment No. 64 of 2010. This study employs normative legal research through statutory, case, comparative, and conceptual approaches. The analysis shows that both states embrace a welfare-state orientation and recognize the protection, promotion, and fulfilment of human rights as a constitutional responsibility of the state. However, Brazil’s explicit formulation provides a stronger basis for justiciability and direct constitutional enforcement, as illustrated by ADPF 709 concerning the Yanomami Indigenous community. By contrast, Indonesia’s implicit formulation allows broader constitutional interpretation and policy flexibility, yet weakens the enforceability of the right to food because the issue is often treated as administrative policy rather than a directly claimable constitutional right. The article argues that Indonesia needs a clearer constitutional or judicial construction of the right to food, supported by minimum standards, complaint mechanisms, and institutional accountability. Such reform is necessary to ensure that access to adequate, safe, and nutritious food is protected not merely as a policy objective, but as an enforceable constitutional entitlement for vulnerable groups.